2017
DOI: 10.3390/met7100443
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Powder Stream on High-Deposition-Rate Laser Metal Deposition with Inconel 718

Abstract: Abstract:For the purpose of improving the productivity of laser metal deposition (LMD), the focus of current research is set on increasing the deposition rate, in order to develop high-deposition-rate LMD (HDR-LMD). The presented work studies the effects of the powder stream on HDR-LMD with Inconel 718. Experiments have been designed and conducted by using different powder feeding nozzles-a three-jet and a coaxial powder feeding nozzle-since the powder stream is mainly determined by the geometry of the powder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 32 publications
2
24
0
4
Order By: Relevance
“…The authors propose that, from this threshold onwards, the increase in carrier gas flow accounts for additional turbulence of the particle stream for which the melt pool and dilution depth are decreased again. Similar findings were presented by Zhong et al [29] who proposed that particle velocity was the dominant factor for melt pool penetration depth when using a three-jet nozzle. Moreover, Shah et al [30] reported an increase of melt pool depth for increasing carrier gas flows.…”
Section: Variation Of Carrier and Shielding Gas Flowsupporting
confidence: 89%
See 1 more Smart Citation
“…The authors propose that, from this threshold onwards, the increase in carrier gas flow accounts for additional turbulence of the particle stream for which the melt pool and dilution depth are decreased again. Similar findings were presented by Zhong et al [29] who proposed that particle velocity was the dominant factor for melt pool penetration depth when using a three-jet nozzle. Moreover, Shah et al [30] reported an increase of melt pool depth for increasing carrier gas flows.…”
Section: Variation Of Carrier and Shielding Gas Flowsupporting
confidence: 89%
“…Apparently, the use of larger shielding gas flow rates facilitates a shallower melt pool. In correlation with the previously seized suggestions of Zhong et al [29], it can be concluded that an increase in shielding gas flow leads to increased interaction and, thus, turbulence with the carrier gas flow, for which the powder particles cannot penetrate the melt pool as deeply as before.…”
Section: Variation Of Carrier and Shielding Gas Flowsupporting
confidence: 76%
“…The typical patterns of powder density and particle temperature distributions were found to be dependent on the coaxial nozzle type by Kovalev et al [20]. Considering all these works, it can clearly be established that the nozzle design and gas parameters have a strong impact on the powder flow density, speed and trajectory, and hence directly influence the powder stream characteristics and the clad efficiency [21].…”
Section: Experimental Conditionsmentioning
confidence: 96%
“…With the relative movement of the laser scanning head and work table, the melt-pool solidifies, resulting in a layer deposition. Layer-by-layer depositions result in a 3D structure [3][4][5].…”
Section: Introductionmentioning
confidence: 99%